Autonomic emotional responses to food: private label brands versus national brands - Rita, P.; Guerreiro, J.; Omarji, M. (Journal of Consumer Behaviour, 2021)
Private label brands (PLB) have been increasing both perceived quality and consumer acceptance in the last decades, which has compelled national brands (NBs) to invest in maintaining consumer confidence and preference. Recent economic crisis led consumers to become more price sensitive and more worried about cutting on daily needs, such as food consumption. However, taste is still one of the most important factor of decision for consumers regarding food products. Despite such importance of taste in decision-making, most research on consumer senses still relies on traditional methods of surveying consumers, which are unable to measure the consumers' autonomic emotional reactions. The current paper uses a psychophysiological method to measure emotional arousal–electrodermal activity (EDA) and a self-assessment manikin to measure pleasure. Emotions are then tested to assess their influence on perceived quality and willingness to buy (WTB). Findings show that NB are still perceived by consumers as superior, but consumers' WTB is not higher for NB. These results show that consumers' decisions are not always in favor of the product which is perceived to have a better quality which suggests that the “quality gap” is fading and the “branding gap” is gaining momentum.